Karakalla w Germanii. Charakter i znaczenie kampanii na pograniczu reńsko-dunajskim z 213 r. - Janiszewska-Sieńko, Daria (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This article is a contribution to the debate on the military campaign of emperor Caracalla in 213 AD in Germania. The author examined historiographic, epigraphic and numismatic sources and focused on the ideological aspects of the Rhine expedition. The conclusion of this article is that there was no military threat on the limes, and the war was only symbolic.
Keywords: Karakalla; Germanie; ideologia wojenna; Sewerowie